The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/jcb.20530
|View full text |Cite
|
Sign up to set email alerts
|

Differential localization of acetylcholinesterase in neuronal and non‐neuronal cells

Abstract: Acetylcholinesterase (AChE) expression is regulated in cell types at the transcriptional and translational levels. In this study, we characterized and compared AChE catalytic activity, mRNA, protein expression, and protein localization in a variety of neuronal (SH-SY5Y neuroblastoma and primary cerebellar granule neurons (CGN)) and non-neuronal (LLC-MK2, HeLa, THP-1, and primary astrocytes) cell types. All cell lines expressed AChE catalytic activity; however the levels of AChE-specific activity were higher in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 52 publications
4
27
0
Order By: Relevance
“…The inhibitors BW284C51 and iso-OMPA have been useful in separating AChE and BuChE activities from the ChE activity, respectively (Bicker et al, 2004;Thullbery et al, 2005). In the present study, the AChE and BuChE activities revealed by each inhibitor perfectly matched the components of ChE activity determined in the absence of any inhibitor.…”
Section: Discussionsupporting
confidence: 72%
“…The inhibitors BW284C51 and iso-OMPA have been useful in separating AChE and BuChE activities from the ChE activity, respectively (Bicker et al, 2004;Thullbery et al, 2005). In the present study, the AChE and BuChE activities revealed by each inhibitor perfectly matched the components of ChE activity determined in the absence of any inhibitor.…”
Section: Discussionsupporting
confidence: 72%
“…Considering localization of the GNDA at the plasma membrane, proteins of the plasma membrane could interact with these substances. Based on the literature reports [23] we supposed that acetylcholinesterase (EC 3.1.1.7; AChE) among others could be a cellular target of GNDAs in the SH-SY5Y cells, therefore effects of GNDAs on the enzyme activity in SH-SY5Y cells were investigated and compared to a tacrine (9-amino-1,2,3,4-tetrahydroacridine) standard, a known inhibitor of acetylcholinesterase [24]. After short 5 min incubation of the cell lysate with GNDAs (0.5 µM), a remaining 52 -72% antiAChE activity was found (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have searched for a potential cellular target for GNDAs in the SH-SY5Y cell line that is being used as a cellular model of cholinergic phenotype [38] with expression of acetylcholinesterase [39][40][41]. AChE is responsible for the termination of cholinergic transmission (breakdown of acetylcholine) [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Since some of these compounds can have anticholinesterase activity, we evaluated whether the phenoxyalkylamino-4-phenylnicotinates (2−7), phenoxyalkoxybenzylidenemalononitriles (12,13), pyridonepezils (14−18), and pyrazolo [3,4-b]quinolines (35−37) were able to prevent the increase in AChE activity ( Figure 5) caused by Aβ 1−42 (2 μM incubated for 24 h) in the neuronal cell line SH-SY5Y, which were shown to have AChE. 58 We have previously reported that Aβ peptides are able to increase AChE in cultured neuronal cells. 57 In this study, we also observed that Aβ 1−42 peptide enhanced AChE activity by about 20%.…”
Section: ■ Results and Discussionmentioning
confidence: 99%